IFC Annual Report 2009 : Their/Our Story, Creating Opportunity Where It's Needed Most - International Finance Corporation (Washington, DC: World Bank, 2012)
The global economic crisis has opened an uncertain chapter, especially for the 2.5 billion people who live on less than $2 a day. Many of them lack access to electricity, or clean water, or basic health care. For at least a decade, economic growth in developing countries helped expand the availability of basic necessities while steadily reducing the number of people in poverty. But this year, the number of people in extreme poverty is expected to be much higher than was predicted before the crisis. Unemployment is rising. Yet many countries lack the domestic resources needed to speed up development. International Finance Corporation (IFC) has responded swiftly and creatively to improve the lives of the most vulnerable people by working with the private sector to create conditions for sustainable prosperity, wherever the need is greatest. IFC has quickly ramped up its advisory efforts and mobilized its donor partners to help governments, clients, and markets cope with the crisis and recover speedily. Priorities include: helping financial institutions better manage their risks and their nonperforming loans; complementing investment efforts in banking for small and medium enterprises, microfinance, and housing finance with advice to financial institutions; supporting governments' efforts to keep trade flowing with advice on trade logistics; helping governments facing larger deficits widen their tax base; encouraging governments to simplify their bankruptcy systems to allow indebted companies to recover faster; advising boards of directors on risk management and crisis intervention; and helping governments redesign public-private infrastructure projects that face crisis-related difficulties.